Economic perspectives of the diversity of risks among crop farmers in the Northern Guinea Savanna of Nigeria - Olarinde, L.O.; Akintola, J.O.; Manyong, Victor M. (Science Alert, 2011)
In this study, we examine the diversity of risks that affect farming in the Northern Guinea Savanna of Nigeria. We also investigate the perspectives of these risks in relation to their economic implications on the farming enterprises. We also show that through reorganization of these risks, some derived factors have the ability to present themselves whether as corresponding to existing categorization of the variables or not and also to enable us know which of the factors is more important than the other. Gross margin and factor analytical methods were used in computing the estimated results on a cross sectional sample of 348 farming households. Results show that farmers who were grouped under natural risk incurred the least mean production cost of 11, 115.61 while the highest mean production cost of 15,998.18 was incurred by farmers grouped under production risks. The highest mean revenue of 18, 998.16 was recorded by farmers under production risk which translated into a mean gross margin of 65,999.85. Verifying whether some derived factors would correspond to the existing categorization of 14 risk types (from five sources) which the farmers faced, results from the factor analysis and the consequent F-test from ANOVA show no marked or significant differences among the identified factors and the existing risk sources. Consequently, the individual effect or importance of the original 14 risk types that the sampled farmers considered important can be dully represented and effectively regrouped into five sources (factors) as natural, technical, social, ecosocial and biochemical.